The Role of Sirtuins in Osteogenic Differentiation of Vascular Smooth Muscle Cells and Vascular Calcification - Wang, Shuangshuang; Hu, Siwang (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification (VC) is a common pathological change in many chronic diseases, such as diabetes and chronic kidney disease. It is mainly deposited in the intima and media of vessels in the form of hydroxyapatite. Recently, a lot of researches have been performed to show that VC is associated with various cellular stresses, such as hyperphosphate, hyperglycemia and oxidative stress. Unfortunately, our understanding of the pathogenesis of calcification is far from comprehensive. Sirtuins belong to a family of class III highly conserved deacetylases that are involved in the regulation of biological and cellular processes including mitochondrial biogenesis, metabolism, oxidative stress, inflammatory response, DNA repair, etc. Numerous studies have shown that sirtuins might play protective roles in VC, and restoring the activity of sirtuins may be a potentially effective treatment for VC. However, the exact mechanism of their vascular protection remains unclear. Here, we reviewed the roles of sirtuins in the osteogenic transformation of vascular smooth muscle cells and the development of VC. We also elucidated the applications of sirtuins agonists for the treatment of VC.